Gerontocracy Revisited. Unilateral Transfer to the Young May Benefit the Middle-Aged - Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2001)
It has been argued that in the absence of altruism, intergenerational transfers can survive only if the old are net recipients. I prove that this need not hold in an over-lapping generations model with a fixed factor. For example, the middle-aged owning land may gain by providing public education even when they cannot tax the young. This requires that labor is not mobile. Furthermore, establishing public education may benefit only the generation which pays for education twice, first for itself and then for the next generation.
Keywords: 330; Intergenerational goods; education; land; gerontocracy